Population dynamics of Megalaspis cordyla (Linnaeus, 1758) from northeastern part of the Bay of Bengal, Bangladesh - Zafar, Mohammad; Mustafa, M G; Haque, M Anna (Indian Journal of Fisheries, 2011)
Population parameters of Megalaspis cordyla from the trawl catches in thenortheastern part of the Bay of Bengal were estimated based on length-frequencydata. The asymptotic length (LÂ°Â°) and growth constant (K) were estimated as 37.90cm (total length) and 0.58/year respectively. The total mortality co-efficient (Z)was 1.75. The estimated natural mortality (M) was 1.17 and the fishing mortalityco-efficient (F) was 0.58. The estimated value for the exploitation rate (E) usingthe length converted catch curve was 0.33. The recruitment was continuous withtwo peaks per year. The sizes of M. cordyla at 25, 50 and 75 per cent probabilitiesof capture were 20.26, 21.80 and 23.34 cm respectively. The length-weightrelationship for combined sex was W=0.01794 TL2818.